Smartdestination: Sebagai Solusi Wisata di Parangtritis Menggunakan Pendekatan Supply Chain Management: Smartdestination: Sebagai Solusi Wisata di Parangtritis Menggunakan Pendekatan Supply Chain Management - Sihombing, Dina Adinda Ronatal (Universitas Duta Bangsa Surakarta, 2024)
Yogyakarta is known as a major tourist destination in Indonesia, especially Parangtritis Beach, one of the tourist attractions in Indonesia that has a strong cultural history located in Kretek District, Bantul Regency, Special Region of Yogyakarta. The existence of Parangtritis Beach tourism not only attracts domestic but also foreign tourists. The difficulty faced is the lack of information about Parangtritis Beach for new tourists. Based on previous research, currently there is no website that promotes Parangtritis Beach with the advantage of cooperation between managers and suppliers of various facilities. The development of the SmartDestination website that popularizes Parangtritis Beach uses information technology as data storage and presentation of tourism information electronically with Supply Chain Management (SCM) management is an innovation that aims to provide convenience for visitors in accessing tourism information and managers in allocating visitors.